Green Synthesis of Zinc Oxide Nanoparticles Using Puerarin: Characterization, Antimicrobial Potential, Angiogenesis, and In Ovo Safety Profile Assessment - Sergio Liga; Raluca Vodă; Lavinia Lupa; Cristina Paul; Nicoleta Sorina Nemeş; Delia Muntean; Ștefana Avram; Mihaela Gherban; Francisc Péter (MDPI AG, 2024)
Background: Zinc oxide nanobiocomposites were successfully synthesized using a green synthesis approach. The process involves the utilization of the isoflavone puerarin, resulting in the formation of PUE-ZnO NPs. Methods: Physico-chemical and biological characterization techniques including X-ray dif-fraction (XRD), UV-vis spectroscopy, Fourier transform infrared spectroscopy (ATR-FTIR), scanning electron microscopy (SEM), atomic force microscopy (AFM), and in ovo methods were employed to study the main characteristics of this novel hybrid material. Results: The PUE-ZnO NPs were confirmed to have been successfully synthesized with a UV absorption peak at 340 nm, the XRD analysis demonstrating their high purity and crystallinity. The energy band-gap value of 3.30 eV suggests possible photocatalytic properties. Both SEM and AFM images revealed the nanoparticle`s quasi-spherical shape, roughness, and size. Good tolerability and anti-irritative effects were recorded in ovo on the chorioallantoic membrane (CAM). Conclusions: According to these results, the synthesis of green PUE-ZnO NPs may be a promising future approach for biomedical and personal care applications.